Structural and Functional Modularity of the U2 snRNP in pre-mRNA Splicing - van der Feltz, Clarisse (Crit Rev Biochem Mol Biol, 2019)
The U2 small nuclear ribonucleoprotein (snRNP) is an essential component of the spliceosome, the cellular machine responsible for removing introns from precursor mRNAs (pre-mRNAs) in all eukaryotes. U2 is an extraordinarily dynamic splicing factor and the most frequently mutated in cancers. Cryo-electron microscopy (cryo-EM) has transformed our structural and functional understanding of the role of U2 in splicing. In this review, we synthesize these and other data with respect to a view of U2 as an assembly of interconnected functional modules. These modules are organized by the U2 small nueclear RNA (snRNA) for roles in spliceosome assembly, intron substrate recognition, and protein scaffolding. We describe new discoveries regarding the structure of U2 components and how the snRNP undergoes numerous conformational and compositional changes during splicing. We specifically highlight large scale movements of U2 modules as the spliceosome creates and rearranges its active site. U2 serves as a compelling example for how cellular machines can exploit the modular organization and structural plasticity of an RNP.